THE INFLUENCE OF ORGANIZATIONAL COMMITMENT AND SELF EFFICACY ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR WITH EMPLOYEE ENGAGEMENT AS AN INTERVENING VARIABLE AT CLASS III AIRPORT OPERATOR OFFICE IN WEST PAPUA - Drajat Perwirajati; Ferdinandus Christian; Anshar Daud (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
Every organization or company operates by using all its resources to produce goods or services that have selling power. The resources owned by a company are required to be able to empower and optimize their use for the continuity of the next company. This study aims to determine the effect of organizational commitment and self-efficacy on organizational citizenship behavior with employee engagement as an intervening variable at the class III airport operator office in West Papua. the sample of respondents was 150 civil servants at the Class III Airport Operator Unit Office in West Papua, based on the Cluster Random Sampling method. The data were tabulated and analyzed using multiple regression methods with the help of SPSS. Causality analysis using Structural Equation Modeling (SEM), Hypothesis testing is done using the AMOS 24 program which can process dimensional and tiered research models. The results showed that organizational commitment (X1) had no effect on employee engagement (Z1). Self efficacy (X2) has a positive and significant effect on employee engagement (Z1), organizational commitment (X1) has a positive and significant effect on organizational citizenship behavior (Z2). Self efficacy (X2) has a positive and significant effect on organizational citizenship behavior (Z2). Employee engagement (Z1) has no effect on organizational citizenship behavior (Z2).